Multi‐parametrical harmonization models in strategic management - Ben-Yair, Avner; Golenko-Ginzburg, Dimitri; Laslo, Zohar (Journal of Business Economics and Management, 2007)
The aim of this paper is to consider a company engaged in designing and creating a new product and, later on, delivering the latter in large quantities to the market. The product is composed of several sub‐products, each of them, in turn, being a subject of several possible versions. The product's utility comprises both the utility of designing and creating the product's pattern example as well as the competitive utility to gain the future commercial success. The problem is to determine the income versions of designing sub‐products in order to maximize the product's competitive utility subject to restrictions related to the design process. A two‐level search algorithm for the problem's solution is suggested. The internal level is faced with optimizing the product's competitive utility by means of experts’ information, while the external level centers on obtaining a routine feasible solution from the point of designing process.First Published Online: 14 Oct 2010